2014
DOI: 10.1016/j.csda.2013.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Modelling trends in road accident frequency— Bayesian inference for rates with uncertain exposure

Abstract: Several thousand people die as a result of a road accident each year in Great Britain and the trend in the number of fatal accidents is monitored closely to understand increases and reductions in the number of deaths. Results from analysis of these data directly influence Government road safety policy and ensure the introduction of effective safety interventions across the country.Overall accident numbers are important, but when disaggregating into various characteristics, accident risk (defined as the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…SPIs based on traffic violations that are used as indicators by some researchers, [20,21], are also a reason for the vagueness of the final score since this type of data can represent the approximate situation on roads but not the precise state of safety and drivers' behavior. Likewise, Lloyd and Forster [22] stated that risk exposures (especially accident risk, which is defined as the rate of accidents per vehicle kilometer traveled) represent uncertain information. Hence, the reliability of the performance index derived from this kind of data is questionable.…”
Section: Uncertain Nature Of Safety Performance Indicatorsmentioning
confidence: 99%
“…SPIs based on traffic violations that are used as indicators by some researchers, [20,21], are also a reason for the vagueness of the final score since this type of data can represent the approximate situation on roads but not the precise state of safety and drivers' behavior. Likewise, Lloyd and Forster [22] stated that risk exposures (especially accident risk, which is defined as the rate of accidents per vehicle kilometer traveled) represent uncertain information. Hence, the reliability of the performance index derived from this kind of data is questionable.…”
Section: Uncertain Nature Of Safety Performance Indicatorsmentioning
confidence: 99%
“…Vehicular mileage or amount of travel is commonly used to quantify exposure (Lloyd & Forster 2014;Naqvi, Quddus & Enoch 2020;Shen et al 2020). WHO (2004) argues that the risk for one journey may be small but that the amount of risk accumulates with each trip.…”
Section: Exposurementioning
confidence: 99%
“…They concluded that fuel prices mediate fatal crashes by reducing exposure as a result of less travel and moderated driver behaviour like speed reduction. Lloyd and Forster (2014) argued that the use of vehicular mileage does not allow for disaggregation, and therefore to overcome this, they simulated both vehicle type and road types to estimate traffic flows. In order to deal with the limitation of disaggregation of travel distance, Shen et al (2020) used the length of driving time to measure exposure, arguing that it is a more reliable measure of exposure.…”
Section: Exposurementioning
confidence: 99%